Appetite regulating hormones in first-episode psychosis: A systematic review and meta-analysis. (July 2019) - Misiak, Błażej; Bartoli, Francesco; Stramecki, Filip; Samochowiec, Jerzy; Lis, Michał; Kasznia, Justyna; Jarosz, Konrad; Stańczykiewicz, Bartłomiej
Highlights: Impaired hormonal regulation of appetite occurs in early psychosis before treatment. Insulin levels are elevated in early psychosis and are related to negative symptoms. Leptin levels are decreased in early psychosis. Alterations of leptin and insulin levels are independent of antipsychotic treatment. Abstract: We aimed to perform a systematic review and meta-analysis of appetite regulating hormones in patients with first-episode psychosis (FEP). Meta-analyses were conducted using random-effects models with Hedges' g as the effect size estimate. We identified 31 eligible studies, investigating the levels of 7 appetite regulating hormones (adiponectin, insulin, leptin, ghrelin, orexin, resistin and visfatin) in 1792 FEP patients and 1364 controls. The insulin levels in FEP patients were higher than in controls (g = 0.34, 95%CI: 0.19 – 0.49, p < 0.001), even considering only antipsychotic-naïve patients (g = 0.39, 95%CI: 0.12 – 0.66, p = 0.005). The severity of negative symptoms was positively associated with the effect size estimates (β = 0.08, 95%CI: 0.01 – 0.16, p = 0.030). Moreover, we found lower levels of leptin in antipsychotic-naïve FEP patients (g = -0.62, 95%CI: -1.11 – 0.12, p = 0.015). Impaired appetite regulation, in terms of elevated insulin levels and decreased leptin levels, occurs in early psychosis, before antipsychotic treatment. Hyperinsulinemia might be related to negative symptoms.